THE USE OF MNEMONIC TECHNIQUEIN IMPROVING STUDENTS' MASTERY OF PAST TENSE: A QUASI-EXPERIMENTAL RESEARCH IN EIGHT GRADE STUDENTSOF A JUNIOR HIGH SCHOOL IN BANDUNG - Firman Sistiawan, - (2011)
Teaching a language cannot be separated from teaching its grammar. Teaching English, therefore involves teaching English grammar as well. Unfortunately, teaching grammar is considered difficult due to its complexity and inappropriate way of teaching it. It is important for English teacher to find out the technique which is appropriate in teaching grammar. Using mnemonic technique seems to be one of interesting techniques in remembering the word changing of past tense and finally the student's comprehension about past tense will increase. This study investigated the effectiveness of using mnemonic technique in improving student's mastery of past tense and students responses to the use of mnemonic technique. Quasi experimental research was used in this study with pre-test and post-test after treatment. The eight graders of a junior high school in Bandung were involved in the study. The sample of this study were two classes, one class as a control group and one class as an experimental group. Each class consists of 30 students. From the findings it was shown that mnemonic technique was effective in improving students past tense mastery as indicated by statistical score in post test of experimental group (M= 73.40), SE (1.93) while post test of control group (M=54.23), SE (2.42). Furthermore, the effectiveness was also supported by student's responses in the questionnaires. The data showed that most of the students of the experimental group felt happy with mnemonic technique in remembering words-change of past tense and automatically this increases student's mastery of past tense. In accordance with the result of the study, the writer recommended for all teachers, not only English teacher to apply mnemonic technique as a technique in remembering something not only tenses form but also other aspects if it is appropriate.